PERANCANGAN PROTOTYPE APLIKASI KNOWLEDGE MANAGEMENT PADA DIVISI MANAGEMENT AUTOMATION INFORMATION UNTUK MENDUKUNG ORACLE FINANCIAL PADA ORANG TUA GROUP - Gema Gema; Celline Liawan; Gerardus Polla (CommIT (Communication and Information Technology) Journal, 2010)
The purpose of this project is to design a knowledge management application as a media to document knowledge and facility that supported a knowledge sharing culture in Oracle Financial subdivision in Orang Tua Group. The researcher uses 7 first steps method which defined by Tiwana in doing knowledge management application prototype. The knowledge management prototype application modules consist of Wiki page, document library, discussion board, blog, picture library, knowledge base, help desk, frequently asked questions, and surveys. In using knowledge in knowledge base, user will get knowledge through business process, how to use the application, or how to finish some cases. Knowledge management prototype application design as a whole could fulfill user’s needs in sharing knowledge, but still needs continuous improvement for maximal usage.Keywords: prototype design, knowledge management application, knowledge